Conceptual Change Level of K-11 Students on the Hydrostatic Pressure Concept Using Virtual Conceptual Change Laboratory - Surtiana, Yunina; Suhandi, Andi; Samsudin, Achmad; Siaahan, Parsaoran; Setiawan, Wawan (Universitas Muhammadiyah Makassar, 2021)
Identification has been carried out to get an overview of the student's Level conceptual change of K-11 student on the hydrostatic pressure concept using Virtual Conceptual Change Laboratory (VCCLab). The VCCLab was created to accomplish the conceptual change level of students’ construction and reconstruction. This investigation aimed to decide the degree of students’ applied change identified in the concept of hydrostatic pressure by involving in VCCLab activities. The strategy utilized was a quantitative enlightening technique which was conducted on a day and a half at class XI-one of the senior high school in West Java Province. The level of students’ conceptual change was identified by using a diagnostic test in the Four - tier test (FTT) format and the results of the students’ worksheets were analyzed based on the guidelines for determining the level of conceptual change. Conceptual change level consists of 1) Scientific conception from the beginning (SCFB); 2) Static (S); 3) Reconstruction (R); 4) Construction (C); and 5) Disorientation (D). The results of the research with VCCLab showed that level 1) scientific conception from the beginning (SCFB) is around 11.1%; 2) Static (S) is around 5.55%; 3) Reconstruction (R) is around 66,7%; 4) Construction (K) is around 16,7% and Disorientation (D) is 0%. In line with the results obtained, it is known that VCCLab can remediate missconception and reach the degree of calculated change in students’ construction and reconstruction.